Blue Jacket Blues: Lost Recordings of Johnny Cash at the Naval War College – Live in ’75 - Kohnen, David; Cash, Jr., Roy (The Northern Mariner / Le marin du nord, 2023)
Sailors far from home often identified with the lyrics of traditional sea shanties, which highlighted the isolation and hard work on an unforgiving sea. Following in this tradition, American sailors also gravitated to the punchy diddy bopper rhythms and bleak lyrical storyline of Cash’s rockabilly classic, “Folsom Prison Blues” Since he scored that first hit in 1955, Cash has cast a very long shadow on American popular culture. Given all that has been written and generally remembered about Cash, many surprises remain unexplored in the remarkable chronology of his life and rise in popular American music. One such example is the previously undocumented performance by the “Man in Black” on St. Patrick’s Day in 1975 at the Naval War College in Newport, Rhode Island. Using recently rediscovered audio from the event, this article examines the concert, as well as the broader influence of Cash upon popular culture, the role of military service upon his work, his intimate connection with the Naval War College, and his broader impact on the United States military. Les marins loin de chez eux s’identifiaient souvent aux paroles des chants de marins traditionnels qui traitaient de l’isolement et du travail acharné sur la mer impitoyable. Reprenant cette tradition, les marins américains étaient également attirés vers les rythmes percutants et le sombre récit du classique du rockabilly de Johnny Cash intitulé «Folsom Prison Blues.» Après avoir connu ce premier succès en 1955, Cash a marqué à tout jamais la culture populaire américaine. Malgré tout ce qui a été écrit et tout ce que nous retenons de Cash, bon nombre de sujets demeurent peu connus dans la chronologie remarquable de sa vie et son grand rôle dans la musique populaire américaine. On peut citer, à titre d’exemple, le spectacle non déjà documenté du chanteur connu sous le nom de « Man in Black » le jour de la St-Patrick en 1975 au Naval War College à Newport, au Rhode Island. À l’aide de l’enregistrement sonore du spectacle qu’on vient de redécouvrir, cet article étudie le spectacle ainsi que l’influence de Johnny Cash sur la culture populaire, le rôle du service militaire sur son œuvre, son lien intime avec le Naval War College et ses répercussions plus vastes sur l’armée américaine.